(3GdfXe GdeSJYPH aj JaSjQ ZQjH CdaGX GdegPHs - (3HWGd Hf CMeO Hf SdjeGf GdQcHis; (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s
(3ChdgG (B:s
(3bGd GdTjN HWGd Hf CMeO bOS Gddg QhMg (B: (3GdMeO ddg Ydi eG Cdge hYde , hHOC Hg ef GdaVd hJeee s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi CKfGA GdcdGe Ydi HGH GdCfaGd , hBNQ eG ajg (B: (3jbGd (B: (3ge Ydjg Ydi LejY Cgd GdCOjGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3Ydi MhGTi GdfSNI JUMjMGJ hebGHdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs